(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The objective of the study was to describe the satisfaction of inpatients with surgical examination and treatment services at Thanh Ba District Health Center, Phu Tho Province in 2024 and some related factors. Method: A cross-sectional descriptive study design with analysis on 382 surgical patients. Data collection techniques as well as quantitative data collection tools were applied according to Decision No. 3869/QD-BYT dated August 28, 2019 of the Ministry of Health on promulgating forms and instructions for surveying patient and medical staff satisfaction. Results: The rate of inpatient surgical treatment had a fairly high satisfaction rate, accounting for 87.5% -92.9% depending on the criteria groups. The average satisfaction score was also very high, from 4.21 - 4.47 points (out of 5 maximum points). Patients with low educational level and without health insurance card have lower satisfaction with medical examination and treatment service than other patients. Conclusion: satisfaction of inpatients with surgical examination and treatment services at Thanh Ba District Health Center is high. Health Center need to focus on improving facilities and take measures to improve satisfaction with patients with low educational level and without health insurance card.